EFFECT OF GOODS DELIVERY CHAIN ON VALIDATION OF ONLINE SALES TRANSACTIONS : (STUDY ON NTB MALL CUSTOMERS IN MATARAM CITY) - Ethic, Sabariah; Saridawati, Saridawati; Suprianto, Agung (Universitas Islam Lamongan, 2023)
Market expansion now does not depend on conventional branch openings, franchises or consignments but is complemented by online sales methods. Problems occur in the identification process of entrepreneurs who do not have assets to deliver goods ordered by consumers online. The scope of research on the supply chain factors for online sales transactions in the validation room. The tools used in the research, the theoretical basis tested into applied cases to be examined in its deductive space as the implementation of the results of input or injection of theory into cases in logical analysis through continuous theoretical enrichment in the field of marketing management in the delivery order and inventory management space. The aim of this research is to provide problem solving through the route of delivery of goods and the regularity of supplies. The problem solving offered in this research is in the inventory identification system in the SME room by using a detailed inventory database and the Delivery Order Security System through the MOU for the process of delivering goods (KURIR), so that a clear route for sending goods is formed such as a computer line.